MОDEL OF DETERMINING STOCK MARKET VOTALITY - BURTNIAK, IVAN; SUDUK, NATALIIA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers different approaches to determining stock market volatility. It is one of the most important indicators of the financial market and characterizes the degree of fluctuations in asset prices, reflects how high the deviations of price changes relative to the general trend. The obtained values of volatility make it possible to analyze the duration of the process in the stock market, make adjustments and concrete steps to improve the situation to optimize the financial strategies of both market participants and economic agents in general. Volatility is an indicator of the meaningfulness of the actions of stock market participants. Thus, volatility is a key concept for assessing market risk and making investment decisions. Derivatives on volatility indicators are very popular among foreign investors. Such instruments allow you to hedge the risks associated with increasing stock market fluctuations, and due to the negative correlation with stock indices increase the benefits of investment diversification if they are in the investment portfolio, especially in a declining market. The calculation of market volatility is based on the following pattern – the size of the option premium directly depends on the current market volatility. The stronger the fluctuations in the market, the greater the risk of the seller of the option, and hence the amount of payment for this risk – the option premium. A further step in the development of volatility indicators is the creation of new derivatives, which means that investors will also be able to hedge risks associated with growing fluctuations in financial markets and earn additional profits by improving the efficiency of portfolio management.
Keywords: volatility; volatility surface; Stock Market; financial market; stock index